Descriptive Study of the Implementation of Primary Health Care Services for Senior Citizens in Surabaya (Indian Journal of Public Health Research & Development, 2020)
Context: High life expectancy in Indonesia also increases as the population of senior citizens increases.The reduction in physical and mental abilities has the potential for older people. The eldercare healthservices are needed to maintain health and productivity. Puskesmas is public providers of primary healthcare in Indonesia. The research was descriptive and observational research. The study population was allpuskesmas in Surabaya city, totaling 63puskesmas. Determination of the sample using disproportionatestratified random sampling method. The number of samples is 25 puskesmas spread in Surabaya City. Thevariables studied were eldercare health services efforts inside and outside the puskesmas. Secondary datawas obtained from the health profile of Surabaya City and primary data was obtained through questionnaires.The implementation of eldercare health services in puskesmas starting from the registration of the elderlyand as many as 15 puskesmashaven’t separate the registration of elderly patients with general patients butgets a special label for registering elderly patients. Outside the puskesmas the form of services is homecareservices that carried out by the majority of puskesmasas many as 16 puskesmas
Keywords: Eldercare, primary healthcare, service providing